Detection of dsRNA-binding domains in RNA helicase A and Drosophila maleless: implications for monomeric RNA helicases. - Gibson, T J (1994)
Searches with dsRNA-binding domain profiles detected two copies of the domain in each of RNA helicase A, Drosophila maleless and C. elegans ORF T20G5-11 (of unknown function). RNA helicase A is unusual in being one of the few characterised DEAD/DExH helicases that are active as monomers. Other monomeric DEAD/DExH RNA helicases (p68, NPH-II) have domains that match another RNA-binding motif, the RGG repeat. The DEAD/DExH domain appears to be insufficient on its own to promote helicase activity and additional RNA-binding capacity must be supplied either as domains adjacent to the DEAD/DExH-box or by bound partners as in the eIF-4AB dimer. The presence or absence of extra RNA-binding domains should allow classification of DEAD/DExH proteins as monomeric or multimeric helicases.